Peningkatan Pengelolaan Keuangan melalui Pelatihan Akuntansi Pembukuan - Fazriyah, Sindy Nur; Julianti, Eka Amelia Chiesa; Maryama, Hanna Meitha; Zalianti, Risma; Damayanty, Prisila (ASOSIASI IDEBAHASA KEPRI, 2025)
The primary objective of basic accounting training is to equip managers of Micro, Small, and Medium-Sized Enterprises (MSMEs) with the skills needed to manage their company's finances more effectively and professionally by focusing on the Basic Accounting Equation. This training was conducted at Warkop Hj Junen in East Jakarta as part of efforts to enhance financial literacy among small business owners. The training covered key topics such as fundamental accounting principles, techniques for recording financial transactions, preparing simple financial reports, and using accounting applications in business operations. The methods employed included interviews, interactive discussions, and case studies tailored to reflect the actual conditions of the participants' businesses. The training aims to deliver lasting benefits, such as improved financial record-keeping skills, better evaluation of business performance, and the ability to develop business strategies based on accurate financial data. Ultimately, this initiative not only promotes financial transparency but also fosters the sustainability and competitiveness of MSMEs in addressing market challenges.